From the editor in chief: The apparatgeist of the moon landing - Jouhki, Jukka (Human Technology, 2019)
July 20, 2019 marks the 50-year anniversary of the moon landing, an event often portrayed as the pinnacle of humankind’s technological achievement. In the editorial, the many ways in which this technological event has been meaningful for people all over the world are discussed. Moreover, the concept of apparatgeist is applied to interpret the significance of the moon landing.